2013
DOI: 10.3892/etm.2013.937
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of plasma miR-146a in sepsis patients compared with non-sepsis-SIRS patients

Abstract: Sepsis is a subtype of systemic inflammatory response syndrome (SIRS), which is characterized by infection. Circulating microRNAs (miRNAs), including miR-150, miR-146a and miR-223, are potential biomarkers of sepsis. In this study, we demonstrated that measuring the relative expression of miR-146a/U6 in plasma, using the 2−ΔΔCt method, provides a method for differentiating between sepsis and non-sepsis-SIRS. We observed a significant increase in miR-146a expression in the initial cohort of 6 non-sepsis-SIRS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 25 publications
7
63
0
Order By: Relevance
“…Key among the dysregulated miRNAs identified in this study is miR-146a, supporting the downregulation observed in a pair of past reports of human sepsis [26, 28]. miR-146a is rich with targets capable of immune modulation.…”
Section: Discussionsupporting
confidence: 88%
“…Key among the dysregulated miRNAs identified in this study is miR-146a, supporting the downregulation observed in a pair of past reports of human sepsis [26, 28]. miR-146a is rich with targets capable of immune modulation.…”
Section: Discussionsupporting
confidence: 88%
“…None of the studies specified the duration of symptoms before inclusion. Nine studies did the initial blood samples at the admission to the ICU [15,16,18,19,25] or within 24 h after admission to the ICU [20,21,23,24]. One study did baseline measurements before LPS infusion [17] and one study did not apply a time of sample collection [22].…”
Section: Resultsmentioning
confidence: 99%
“…In 8/13 studies [16e18,20,23e26] the authors searched mainly for pre-defined miRs while in the rest of the studies [15,19,21,22,27] a pre-experimental testing on survivors/non-survivors or animals were made before determining which miRs to investigate in the validation population look. Four studies [15,20,23,25] compared patients with sepsis with patients with SIRS. One study [17] analysed changes in miR-expression in three male healthy volunteers after endotoxemia induction, using lipopolysaccharides from gram positive bacteria to simulate sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, another study, using RT-PCR, examined the differential expression of miR-146a in plasma samples of 14 non-sepsis SIRS patients and 14 sepsis patients. The investigators observed higher levels of serum miR-146a in non-sepsis SIRS patients compared to sepsis patients [32]. Hence, these studies suggest that miR-146a and miR-223 may be optimal diagnostic tools for sepsis.…”
Section: Extracellular Micrornas As Potential Biomarkers In Sepsismentioning
confidence: 99%